Identification and classification of risk factors for mental health problems in healthcare workers using a systemic framework: an umbrella review - Payam Khanlari; AhmadAli NoorbalaTafti; Fakhradin Ghasemi; Shahrzad Ghiyasvandian; Kamal Azam; Seyed Abolfazl Zakerian (BMC Public Health)
Abstract Background Mental health problems are high among healthcare workers (HCWs) due to difficult and complex working conditions. This study aims to investigate the prevalence of depression and anxiety through existing meta-analyses and identify risk factors related to these mental health issues at different levels of the work system. Methods We conducted an umbrella review with a scoping approach to identify and select studies related to depression and anxiety among HCWs. This study was conducted according to a five-step scoping approach. The search included only studies published before January 2024. The final studies were reviewed and selected using EndNote X9, with information extracted according to specific criteria. Results Sixty-one studies were included in the final stage and necessary information was extracted from them, 47 articles reported prevalence and risk factors were extracted from 29 articles. Most of the studies were conducted in the context of Covid-19. prevalence of depression varied between 20.5% and 46.2% and for anxiety, it was between 21.9 and 47%. Factors related to depression and anxiety were divided into four levels of the work system, including individual factors, work and unit factors, organizational factors, and external factors. Conclusions Numerous secondary studies indicate a high prevalence of depression and anxiety among HCWs, especially during the COVID-19 pandemic. This study introduces a framework for systematically identifying mental health problems. Future research is encouraged to utilize this framework to identify risk factors contributing to mental health challenges. It is recommended to use a systemic approach to managing mental health problems.